2012
DOI: 10.1364/oe.20.019484
|View full text |Cite
|
Sign up to set email alerts
|

Giant tunable Faraday effect in a semiconductor magneto-plasma for broadband terahertz polarization optics

Abstract: Abstract:We report on a giant Faraday effect in an electron plasma in nInSb probed via polarization-resolved terahertz (THz) time-domain spectroscopy. Polarization rotation angles and ellipticities reach as large as π/2 and 1, respectively, over a wide frequency range (0.3-2.5 THz) at magnetic fields of a few Tesla. The experimental results together with theoretical simulations show its promising ability to construct broadband and tunable THz polarization optics, such as a circular polarizer, half-wave plate, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 36 publications
(57 reference statements)
0
51
0
Order By: Relevance
“…Depending on the data acquisition speed, experiments that require the magnetic field dependence can be swept from 0-30 T within a single magnet pulse, and then repeated to improve the signal-to-noise ratio by averaging. The optical access via interchangeable windows allows us to introduce a variety of wavelengths, and, importantly, the application most suited for this magnet will be time-domain terahertz spectroscopy [7][8][9][10][11][12][13][14][15] because of the compact design and direct optical access to the sample. Furthermore, the direct optical access allows polarizationsensitive measurements 14,44 without the complications that arise with optical fibers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Depending on the data acquisition speed, experiments that require the magnetic field dependence can be swept from 0-30 T within a single magnet pulse, and then repeated to improve the signal-to-noise ratio by averaging. The optical access via interchangeable windows allows us to introduce a variety of wavelengths, and, importantly, the application most suited for this magnet will be time-domain terahertz spectroscopy [7][8][9][10][11][12][13][14][15] because of the compact design and direct optical access to the sample. Furthermore, the direct optical access allows polarizationsensitive measurements 14,44 without the complications that arise with optical fibers.…”
Section: Discussionmentioning
confidence: 99%
“…The optical access via interchangeable windows allows us to introduce a variety of wavelengths, and, importantly, the application most suited for this magnet will be time-domain terahertz spectroscopy [7][8][9][10][11][12][13][14][15] because of the compact design and direct optical access to the sample. Furthermore, the direct optical access allows polarizationsensitive measurements 14,44 without the complications that arise with optical fibers. Finally, the mini-coil design can be reproduced by other researchers around the world and incorporated into setups that already use expensive ultrafast laser systems or other sophisticated optical systems, greatly expanding the availability of high magnetic fields for condensed matter and materials research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Narrow-gap semiconductors and semimetals show giant free-carrier Faraday effect in the THz frequency range [20][21][22]. Here, we review recent reports on the giant Faraday effects observed in n-InSb, HgTe, and grapheme in the THz frequency range and discuss their potential as THz polarization optics, such as circular polarizers, wave plates, isolators, and modulators.…”
Section: Giant Faraday Effect In Narrow-gap Semiconductors and Semimementioning
confidence: 99%
“…In spite of this, some recent progresses in this field have been reported. For examples, the giant Faraday rotations were observed in some high electron mobility semiconductors, such as InSb, 8 HgTe, 9 and graphene. 10 A magnetically induced THz transparency (a sudden appearance and disappearance for THz transmission) in the n-doped InSb was demonstrated, owing to the interference between left and right circularly polarized magnetoplasmon (MP) eigenmodes.…”
mentioning
confidence: 99%